Real-Time Optical pH Sensor with CMOS Contact Imaging and Microfluidics - Cao M.; Mahto S.K.; Yadid-Pecht O. (My University, 2025)
An optical contact pH sensor integrated with capillary microfluidics is proposed in this paper. The complementary metal-oxide-semiconductor sensing array detects the changes of light intensity after absorption by a phenol red-doped sol-gel filter, while the level of absorbance corresponds to a pH value of the analyte. The optical signal is analyzed by image processing to compare the change in intensity of the filter following sample introduction, thereby obtaining the actual pH value. Deposition methods of sol-gel are optimized and compared. A spin-coating screen-printing process is proposed and tested for creating thin and crack-free sol-gel patterns. Two similar phenol red-doped sol-gel filters are patterned on the same sensor array to collect more precise results. This system offers the capability to perform an optical-based multi-parametric detection. Capillary microfluidics is utilized to enable a real-time flow in and out of the sample, as well as, for establishing more precise control over the sample introduction. © 2015 IEEE.